Método Pold como tratamiento fisioterapéutico de la cervicalgia del adulto. Hospital Básico Dr. Publio Escobar Gómez, 2018 - Verdezoto García, Anderson Cristóbal (2019)
The project of investigation consisted of applying the Method Pold by means of oscillatory movements, to diminish the pain in patients with cervicalgia mechanics that there came to the Basic Hospital Dr. Publio Escobar Gómez; It was realized in 25 patients by the above mentioned pathology to which fisioterapéuticas applied clinical histories for the obtaining of general information necessary for the statistical process, to identify the painful initial and final condition there was used the analogical visual scale (EVE) which you sewed in a line of 10 cm that represents the range pain perceived by the paciente.se there used the method Pold with a dosing of 1 time a day during 30 minutes. The analysis of results obtained by means of the statistical study of the information obtained across clinical history fisioterapéutica and the analogical visual scale (EVE), was achieved to identify that the patients' kind over that they predominate is feminine, this can be for the labor activities as housewives, farmer, merchants leading them to having a routine and sressful way of life. In the check of the results comparing the initial evaluation with the final there was obtained by means of the application of the scale (EVE), that 24% of patients does not present pain, 36% I diminish his pain to slightly, 32% presents a moderate pain and 8% an intense pain demonstrating that the method pold for cervicalgia mechanics is effective.